Thermally Induced Transformation of Nonhexagonal Carbon Rings in Graphene-like Nanoribbons - Liu, Meizhuang; Liu, Mengxi; Zha, Zeqi; Pan, Jinliang; Qiu, Xiaohui; Li, Tao; Wang, Jiaobing; Zheng, Yue; Zhong, Dingyong (Journal of physical chemistry. C, 2018)
Exploring the structural transformation of nonhexagonal rings is of fundamental importance for understanding the thermal stability of nonhexagonal rings and revealing the structure–property relationships. Here, we report on the thermally induced transformation from the fused tetragon-hexagon (4–6) carbon rings to a pair of pentagon (5–5) rings in the graphene-like nanoribbons periodically embedded with tetragon and octagon (4–8–4) carbon rings. A distinct contrast among tetragon, pentagon, hexagon, and octagon carbon rings is provided by noncontact atomic force microscopy with atomic resolution. The thermally activated bond rotation with the dissociation of the shared carbon dimer between the 4–6 carbon rings is the key step for the 4–6 to 5–5 transformation. The energy barrier of the bond rotation, which results in the formation of an irregular octagon ring in the transition state, is calculated to be 1.13 eV. The 5–5 defects markedly change the electronic local density of states of the graphene-like nanoribbon, as observed by scanning tunneling microscopy. Our density functional theory calculations indicate that the introduction of periodically embedded 5–5 rings will significantly narrow the electronic band gap of the graphene-like nanoribbons.